SIRT1 regulates MAPK pathways in vitiligo skin: insight into the molecular pathways of cell survival. Issue 3 (10th January 2014) - Becatti, Matteo; Fiorillo, Claudia; Barygina, Victoria; Cecchi, Cristina; Lotti, Torello; Prignano, Francesca; Silvestro, Agrippino; Nassi, Paolo; Taddei, Niccolò
Abstract Vitiligo is an acquired and progressive hypomelanotic disease that manifests as circumscribed depigmented patches on the skin. The aetiology of vitiligo remains unclear, but recent experimental data underline the interactions between melanocytes and other typical skin cells, particularly keratinocytes. Our previous results indicate that keratinocytes from perilesional skin show the features of damaged cells. Sirtuins (silent mating type information regulation 2 homolog) 1, well‐known modulators of lifespan in many species, have a role in gene repression, metabolic control, apoptosis and cell survival, DNA repair, development, inflammation, neuroprotection and healthy ageing. In the literature there is no evidence for SIRT1 signalling in vitiligo and its possible involvement in disease progression. Here, biopsies were taken from the perilesional skin of 16 patients suffering from non‐segmental vitiligo and SIRT1 signalling was investigated in these cells. For the first time, a new SIRT1/Akt, also known as Protein Kinase B (PKB)/mitogen‐activated protein kinase (MAPK) signalling has been revealed in vitiligo. SIRT1 regulates MAPK pathway via Akt‐apoptosis signal‐regulating kinase‐1 and down‐regulates pro‐apoptotic molecules, leading to decreased oxidative stress and apoptotic cell death in perilesional vitiligo keratinocytes. We therefore propose SIRT1 activation as a novel way of protecting perilesional vitiligo keratinocytes from damage.